2021
DOI: 10.1016/j.humimm.2021.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Administration of high titer convalescent anti-SARS-CoV-2 plasma: From donor selection to monitoring recipient outcomes

Abstract: Early in the SARS-CoV-2 pandemic, convalescent plasma (CP) therapy was proposed as a treatment for severely ill patients. We conducted a CP treatment protocol under the Mayo Clinic Extended Access Program at University Hospital Brooklyn (UHB). Potential donors were screened with a lateral flow assay (LFA) for IgM and IgG antibodies against the SARS-CoV-2 S1 receptor-binding domain (RBD). Volunteers that were LFA positive were tested with an ELISA to measure IgG titers against the RBD. Subjects with titers of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…For comparative purposes HLA typing was also performed on 40 convalescent plasma (CP) donors who had had mild COVID-19 symptoms, were never hospitalized and volunteered to donate CP. Inclusion criteria for CP donors was a previous positive RT-PCR test for SARS-CoV-2 and/or detectable antibodies to SARS-CoV-2 of either the IgM type, IgG type or both [18] . HLA typing of 40 CP donors for the A, B, C, DRB1, 3, 4, 5, DQA, DQB, DPA and DPB loci is shown in Supplementary Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For comparative purposes HLA typing was also performed on 40 convalescent plasma (CP) donors who had had mild COVID-19 symptoms, were never hospitalized and volunteered to donate CP. Inclusion criteria for CP donors was a previous positive RT-PCR test for SARS-CoV-2 and/or detectable antibodies to SARS-CoV-2 of either the IgM type, IgG type or both [18] . HLA typing of 40 CP donors for the A, B, C, DRB1, 3, 4, 5, DQA, DQB, DPA and DPB loci is shown in Supplementary Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The Downstate Institutional Review Board (IRB) reviewed and approved the studies in this report (IRB #1232938-3 and IRB #341403-1). Characteristics of patients given CP and those not given CP as well as CP donor characteristics were previously published [18] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] Mendoza found that death was a less frequent outcome for patients that received high titer CP (>1:1024) 38.6% mortality than patients that received low titer CP (1:1024) 77.8% mortality. [18] The volume of plasma that should be administered per kg of body weight depends on the antibody titer. For instance, 5 mL/kg plasma is required with an antibody titer ≥1:160.…”
Section: The Potential Efficiency Of Cp Dose Adjudgmentmentioning
confidence: 99%